Hirschsprung's Disease Presenting as Neonatal Appendicitis - Lassaad Sahnoun; Mourad Kitar; Kais Maazoun; Amine Ksia; Jamila Chahed; Mongi Mekki; Imed Krichen; Mohsen Belghith; Abdellatif Nouri (EL-Med-Pub, 2013)
See Fulltext